Attraction of Rhyssomatus nigerrimus (Fahraeus) (Coleoptera: Curculionidae) to Odors from Alternate Host Plants - López-Guillén, Guillermo; Cruz-López, Leopoldo; Joyce, Andrea (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The soybean weevil Rhyssomatus nigerrimus (Fahraeus), is an economically important pest that attacks soybean (Glycine max (L.) Merrill] crops in northern and southern Mexico. Rhyssomatus nigerrimus can be considered a specialist insect because it selects soybean plants for its reproduction and feeding. However, when the rainy season begins, new emerged adult weevils can feed and take refuge in other alternate host plants, such as Rottboellia cochinchinensis (Lour.) W. Clayton, Hyparrhenia rufa (Nees) Stapf, Sorghum halepense (L.) Persoon and Ipomoea trifida (Kunth) G. Don when soybean is not available. These host plants can potentially be used as attractant plants. The objectives of this study were a) to determine the attraction response of adult R. nigerrimus to four species of alternate host and their volatiles extracts, b) to identify the volatile compounds present in each alternate host plant species volatiles extracts, and c) to determine the antennal response (EAG) of female and male R. nigerrimus to volatiles extracts from the alternate host plants. The attraction bioassays were conducted in an arena, on which we evaluate the R. nigerrimus response to foliage and extract of the alternate host plants. The antennal response of R. nigerrimus females and males to volatiles from alternate host plants was determined by the electroantennogram (EAG) technique. Female and male R. nigerrimus were more attracted by the foliage and extracts from I. trifida, R. cochinchinensis, H. rufa and S. halepense than to the control. The strongest EAG response of female and male R. nigerrimus was observed with the volatiles from S. halepense, H. rufa, I. trifida and R. cochinchinensis. The control elicited the weakest antennal response. The GC-MS analysis of the volatile compounds from I. trifida, S. halepense, H. rufa and R. cochinchinensis revealed the presence of 17, 9, 9 and 9 compounds, respectively. Major volatiles compounds could be used as lures in traps to control R. nigerrimus.